O desenvolvimento além do esperado dos bolsistas PROUNI: um enfoque psicológico sob a luz das teorias motivacionais humanas - Avelino, Laiza Pâmela Rodrigues Soares (2017)
Starting with the Federal Constitution of 1988, a series of social rights was established for Brazilian citizens, one of them being education. Since then, progress has been made in the consolidation of this right, such as the expansion of access to higher education (HE). In Brazil, one of the instruments that make up the HE assessment is ENADE - Exame Nacional de Desempenho dos Estudantes. When analyzing its micro data, it is verified that, in certain courses, ProUni students, generally from the most vulnerable socioeconomic classes and holders of a low background, have presented superior academic performance when compared to their paying peers, as a rule coming from wealthier socioeconomic classes and holders of a high background. Furthermore, in addition to this reality, a series of studies has found that students from lower classes have also demonstrated superior school performance. The micro data from ENADE and the recent literature on the subject conflict directly with the consolidated literature of Pierre Bourdieu's Theory of Cultural Capital and with the researches in school effectiveness, because according to this theory it is expected that facing the same school factor, students with low cultural capital present lower educational performance than students of high cultural capital, in the case, ProUni students and paying students, respectively. Faced with this apparent contradiction, the present research aimed to verify to what extent the higher academic performance of ProUni students in relation to their paying peers could be explained by human motivational factors (psychological approach). As a methodological outline there was: initial review of the literature; selection of non-probabilistic sample of the intentional type (thirteen students from the third, fifth, sixth and eighth period of the Management course of a HE institution from the countryside of RS); Semi-structured interview application and socio-demographic questionnaire for data collection, as well as the use of content analysis for interlocution between the theoretical framework and the empirical data mapped. This study has also discussed about the social right to Education, pointing out the trajectory of public educational policies in HE in Brazil, the democratization of access to HE, the programs and projects that popularized its expansion, specifying and detailing ProUni. The current human motivational theories that are more persistent in the investigation of motivation to learn were characterized, being: the Theory of attribution of causality, the Theory of self-determination, Theories of self-efficacy and self-regulation and Theory of achievement goals. The sociodemographic profile of the sample studied and the empirical content of the semi-structured interviews were presented. Thus, it was found that this research sample named the effort as the main explanatory factor for its academic success/failure; Autonomous motivation; They believe that their academic achievements result from the persistent use of their efforts, even if they face difficulties, they set goals, and make use of effective learning strategies; And are meta learning oriented. Therefore it is possible to consider that the motivation to learn is an explanatory factor for the better academic performance of these students.